Low-temperature complete oxidation of CO over various manganese oxide catalysts - Dey S.; Dhal G.C.; Mohan D.; Prasad R. (My University, 2025)
The low temperature catalytic oxidation of CO conceivably the most extensively studied reaction in the history of heterogeneous catalyst and it is important in the context of cleaning the air and lowering the automotive emissions. Among a variety of manganese oxides catalyst, the Mn2O3 is considered to be the most favorable with respect to the catalytic activity. A novel route of reactive calcination (RC) of Mn-salts (Mn-Acetate and Mn-Nitrate) for the synthesis of highly active catalysts was studied. The calcination of the precursor produced manganese oxide species (Mn2O3 and MnO2) in thermodynamic equilibrium, with the major nano-size Mn2O3 phase having a large surface area, and lower crystallinity. The amazing activity of the novel MnOx catalysts over the conventional ones obtained by calcination of the precursors in stagnant air, flowing air and reactive calcination (4.5%CO in air) in CO oxidation was associated with the presence of Mn2O3 and its unusual morphology as evidenced by XRD, SEM-EDX, XPS and FTIR characterization. The catalysts obtained by calcination of various MnOx precursors showed activity for the CO oxidation in the following order: Mn-Acetate > Mn-Nitrate and all the traditional route of calcination was also followed the same activity order. Further, the activity order of the catalysts obtained by various calcination conditions was as follows: RC > flowing-air > stagnant-air. © 2018